A comparison between risk assessments methods: assessing five species of cloud forest rodents in Mexico - Ramirez,Rafael S; Quintero,Esther (PeerJ PrePrints, 2015)
Background. Red Lists have been traditionally used as the instruments to guide conservation strategies to avoid extinctions. There is little objection to the idea that categorizing species according to their risk of extinction is a good way to prioritize and implement conservation actions; however, there is little consensus in the best way to do this categorization, and different countries have developed different methods according to their specific needs. The scope of this paper is to contrast the Mexican Risk of Extinction Assessment Method (MER) and the one used by the IUCN Red List, and test how simple, objective and transparent are them. Methods. In order to compare the we performed a search within IUCN´s data base to find species ranked as critically endangered which have not been assessed by the MER. We picked 5 species from the rodent genus Habromys and performed a literature review to assess them through the MER guidelines; we then compared the outcomes with UICN Red List. Results. The five assessed species of cloud forest rodents yield equivalent results through both the MER and IUCN assessments; however, the information asked for by the MER was scant for all the species, and we argue that the results of the assessments are thus not entirely objectives. Moreover, we found that the MER is not a simple method to use due to ambiguities of the criteria. Discussion. The aim of risk assessments is to clearly define the conservation status of a given species, displayed in a simple, transparent, objective, way, which can be relevant in terms of scope and impact on conservation actions. Unfortunately the MER does not fulfil all these requirements, potentially compromising conservation actions. As a result, we propose that it is time reevaluate the current version of the Mexican Risk of Extinction Assessment Method.
Keywords: species risk assessment; conservation actions; IUCN Red List; MER; Cloud Forest; frugivorous rodents